In teamwork, is the whole sum of the parts? - Rosalinda Arroyo-Hernández; Isaac Camacho-Miranda; Eduardo Fernández-Nava; José Vladimir Ruíz-Pérez; Daniela Sarahi Anaya-Lima (Interacciones)
Teamwork is one of the most common educational strategies in Higher Education Institutions, documenting widely that cooperative learning has advantages in terms of individual performance, comprehensive knowledge, school performance and even in school adaptation. Even though it has its benefits, the general analysis concentrates on the product that is the result of teamwork, there is little systematic work about the process, that is, the way in which individual competences are intertwined to satisfy group criteria. A first step in this direction requires the specific identification of individual competence in each member of a team and to later observe how they are coordinated given a collective task. In this sense, a study was conducted with dyads of participants whom were identified as having compatible (same functional type) or incompatible (different functional type) which were exposed to a task that required the conjoint performance of both members of the dyad, the task could either correspond o not correspond with the competence primacy identified for such dyads members. Results are analyzed in terms of the correspondence between task complexity and competence primacy of dyad members. Conclusion are drawn as to the possible educational implications for work team organization.